Efektivitas Evaluasi Administrasi Pendidikan dalam Mendukung Pelayanan Masyarakat - Adinata Rusmen Idris; Julia Muryani; Diana Anggraini; Chusnul Chotimah; dwijulyanto999@gmail.com; Sahrur Rhomadon (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to examine the role of educational administration evaluation in improving the quality of academic services in schools. This study applies a qualitative approach based on a literature review sourced from various national and international journals, reference books, and the results of relevant previous studies. The analysis was conducted using content analysis techniques, with the stages of identifying, grouping, and interpreting findings from the reviewed literature. The research findings reveal that educational administration evaluation plays a crucial role in improving the quality of school governance, particularly in the dimensions of planning, implementation, and administrative oversight. Structured and consistent evaluation allows for the identification of weaknesses in the administrative system and serves as a foundation for improving academic services. Furthermore, the effectiveness of evaluation is determined by several factors, including the competence of administrative staff, the commitment of the principal, the adequacy of facilities and infrastructure, and the application of information technology. These factors simultaneously contribute to the quality of academic services in schools. Therefore, an effective educational administration evaluation will promote administrative work efficiency and strengthen the delivery of more optimal and high-quality academic services in the school environment.